Rupelian Fossil Elasmobranch from Omani Thaytiniti Fauna Fill A Chronological Gap in The Elasmobranch Fossil Record of West Indian Ocean - Sylvain, Adnet; Henri, Cappetta; Vincent, Charpentier (The Journal of Oman Studies, 2023)
In 1990’s, French-Omani team first signalled in southern part of Dhofar, South Oman, several terrestrial vertebrates mixed with marine members in an Early Oligocene fossil assemblage. Even though most of these fossils have been reported and published by palaeontologists, fossil elasmobranchs (sharks and rays) have deserved little attention since this date. In this paper we describe and figurate the elasmobranch members recovered during the 90’s fieldtrips at Thaytiniti and which includes several requiem sharks (Carcharhinus perseus; Negaprion, Rhizoprionon), snaggletooth shark (Hemipristis, Moerigaleus), nurse and zebra shark (Nebrius, cf. Stegostoma); bamboo shark (Chiloscyllium), tiger shark (Galeocerdo); wedgefish and guitarfish (Rhynchobatus; Rhinobatos) and several stingrays (e.g. Himantura,?Taeniura), cownose and eagle rays (Rhinoptera, Aetobatus). Together with the fossiliferous outcrops at Paali Nala, Pakistan, the Oman locality Thaytiniti fill the chronological gap in the fossil record of West Indian Ocean elasmobranch communities. Their resembling elasmobranch assemblages constitute an original and significant amount of new elements about the Late Paleogene tropical ichtyofauna living close to estuaries and support that the settlement of the modern Indian Ocean fish fauna occur during Early Oligocene to Early Miocene period as these sites interestingly mostly present members known in present Indian Ocean.